2022
DOI: 10.1038/s41598-022-08871-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV-reservoir size is not affected either by HCV coinfection or by direct acting antivirals (DAAs) therapy

Abstract: The role of HCV on the HIV reservoir is controversial since the reduction on HIV-DNA levels after HCV eradication with IFNα/RBV treatment seems to be the result of drugs instead of HCV clearance. We assessed whether HCV eradication can decrease HIV-DNA content in HIV/HCV-coinfected patients treated with direct-acting antivirals, DAAs (IFNα/RBV-free regimens). Cell-associated HIV-DNA was measured by ddPCR in 25 HIV-monoinfected and 25 HIV/HCV-coinfected patients. There were no differences in HIV-DNA levels betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…While it has been found that the HIV-1 reservoir remains stable after the administration of DAAs in coinfected subjects [24][25][26], this is the first study carried out in rCD4+ T cells, the main HIV reservoir. Our results contrast with those observed by Álvarez and colleagues [27] who did not observe differences between HIV-monoinfected and -coinfected individuals. Differences relating to patients' inclusion and exclusion criteria, Fiebig stage, time since HIV diagnosis, cells in which proviral DNA was quantified, and the different methodology used could explain the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…While it has been found that the HIV-1 reservoir remains stable after the administration of DAAs in coinfected subjects [24][25][26], this is the first study carried out in rCD4+ T cells, the main HIV reservoir. Our results contrast with those observed by Álvarez and colleagues [27] who did not observe differences between HIV-monoinfected and -coinfected individuals. Differences relating to patients' inclusion and exclusion criteria, Fiebig stage, time since HIV diagnosis, cells in which proviral DNA was quantified, and the different methodology used could explain the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…The population included in the present study consisted of HIV-infected patients, who all received successful long-term ART and exhibited high CD4 + T-cell counts. We provide prospective information on pathogenic or immunovirological aspects related to systemic in ammation, T-cell function and homeostasis and reservoir size 30,41,49 for this cohorts of both coinfected and monoinfected individuals.…”
Section: Strengthsmentioning
confidence: 99%